Strategi Kepala Sekolah SDN Pejagan 9 Bangkalan dalam Memitigasi Learning loss Pasca Pandemi Covid-19: Indonesia - Muhammad Haykhal Priambudhi; Lailatul Mukarromah; Agung Setyawan (LLDIKTI WILAYAH XIII, 2025)
This study aims to analyze the strategies implemented by the principal of SDN Pejagan 9 Bangkalan in mitigating learning loss after the Covid-19 pandemic. Using a qualitative approach with an interview method, data were collected from the principal as the main informant. The findings reveal that learning recovery was carried out through three main strategies: blended learning using teacher-made instructional videos and WhatsApp communication, limited face-to-face learning combined with home visits, and additional learning sessions focused on reinforcing core materials. These strategies successfully reduced disparities in students’ understanding, improved motivation, and strengthened collaboration between schools and parents. The use of simple digital media proved effective in maintaining learning continuity in limited technological environments. The study highlights the crucial role of school leadership in coordinating adaptive and participatory approaches to ensure meaningful learning. It concludes that a collaborative and flexible leadership model can foster a resilient learning system capable of responding to future educational crises.